Practical Chronic Pain Assessment Tools in Clinical Practice - Mirjana Lončarić-Katušin; Milan Milošević; Antonio Žilić; Petar Mišković; Višnja Majerić-Kogler; Josip Žunić (Acta Clinica Croatica, 2016)
The aim of the study was to show the role of tools in the evaluation of chronic pain (CP) in general practitioner (GP) everyday clinical practice. The study was done by analyzing electronic database of the first visits of 1090 CP patients referred to the Pain Clinic of the Karlovac General Hospital, Karlovac, Croatia, by their GPs. All patient records were analyzed according to the cause of CP, strongest pain a week before the examination, quality of sleep, and the Patients’ Global Impression of Change scale. All statistical analyses were done using the IBM SPSS Statistics version 19.0.0.1 (www.spss.com). CP predominantly occurs in older age group. Patients with musculoskeletal pain accounted for the highest percentage (n=316; 29%), followed by those with neuropathic pain (n=253; 23.20%) and those with low back pain (n=225; 20.60%). The mean pain intensity rating scale score was 8.3±1.8 a week before the examination and the mean quality of sleep score was 6.8±1.9. Moderate and severe sleep quality disorder was significantly present in patients over 65 years of age (p=0.007), patients with musculoskeletal and neuropathic pain, back pain, and those having rated Patients’ Global Impression of Change scale as worsening (p=0.001). The severity of pain and poor quality of sleep are the leading causes of deterioration of the Patients’ Global Impression of Change scale in patients suffering from musculoskeletal and neuropathic pain. In order to treat CP comprehensively, it is important for GPs to evaluate the outcomes of clinical treatment using tools for CP assessment.